Bonding behavior and chemical and mechanical properties of silver-based dental alloys - Hiroshi Shimizu; Yoshimasa Takeuchi (Elsevier, 2021)
This article presents a review of silver-based dental alloys, with a focus on their bonding behavior and their chemical and mechanical properties. The most effective pretreatment for bonding silver-based alloys involves alumina air-abrasion followed by the application of a metal adhesive primer containing both the vinyl-thione monomer and a hydrophobic phosphate monomer. Silver-based alloys are readily sulfurized, making it clinically important to limit their use to cast post and core restorations to avoid direct exposure to salivary components. Fracture of the post and core restorations can be prevented by reinforcing their mechanical properties by applying the cast joining technique with tougher metals.